Comparative Analysis of Carbon Monoxide Tolerance among Thermoanaerobacter Species - Alves, Joana I.; Alves, M. Madalena; Plugge, Caroline M.; Stams, Alfons J. M.; Sousa, Diana Z. (Frontiers in Microbiology, 2016)
An anaerobic thermophilic strain (strain PCO) was isolated from a syngas-converting enrichment culture. Syngas components cannot be used by strain PCO, but the new strain is very tolerant to carbon monoxide (pCO = 1.7x105 Pa, 100% CO). 16S rRNA gene analysis and DNA-DNA hybridization revealed that strain PCO is a strain of Thermoanaerobacter thermohydrosulfuricus. The physiology of strain PCO and other Thermoanaerobacter species was compared, focusing on their tolerance to carbon monoxide. T. thermohydrosulfuricus, T. brockii subsp. finnii, T. pseudethanolicus and T. wiegelii were exposed to increased CO concentrations in the headspace, while growth, glucose consumption and product formation were monitored. Remarkably, glucose conversion rates by Thermoanaerobacter species were not affected by CO. All the tested strains fermented glucose to mainly lactate, ethanol, acetate and hydrogen, but final product concentrations differed. In the presence of CO, ethanol production was generally less affected, but H2 production decreased with increasing CO partial pressure. This study highlights the CO resistance of Thermoanaerobacter species.